2023
DOI: 10.3389/fmed.2022.1070072
|View full text |Cite
|
Sign up to set email alerts
|

PathNarratives: Data annotation for pathological human-AI collaborative diagnosis

Abstract: Pathology is the gold standard of clinical diagnosis. Artificial intelligence (AI) in pathology becomes a new trend, but it is still not widely used due to the lack of necessary explanations for pathologists to understand the rationale. Clinic-compliant explanations besides the diagnostic decision of pathological images are essential for AI model training to provide diagnostic suggestions assisting pathologists practice. In this study, we propose a new annotation form, PathNarratives, that includes a hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Such collaborative efforts, where the human-AI team outperforms the individual agents acting separately, are also called hybrid intelligence [32,33]. Examples of such effective human-AI collaboration include knowledge work [34], data annotation [35], medical diagnosis [36], mental health [37], and computationally informed mission planning [38]. Furthermore, the new developments in the theory of organizational decision-making [39] also suggest effective ways in which the decisions of organizational members can be combined with AI-based decisions for successful human-AI teaming and collaboration in the project management area.…”
Section: Human-ai Collaboration In Project Managementmentioning
confidence: 99%
“…Such collaborative efforts, where the human-AI team outperforms the individual agents acting separately, are also called hybrid intelligence [32,33]. Examples of such effective human-AI collaboration include knowledge work [34], data annotation [35], medical diagnosis [36], mental health [37], and computationally informed mission planning [38]. Furthermore, the new developments in the theory of organizational decision-making [39] also suggest effective ways in which the decisions of organizational members can be combined with AI-based decisions for successful human-AI teaming and collaboration in the project management area.…”
Section: Human-ai Collaboration In Project Managementmentioning
confidence: 99%
“…Fourth, low awareness and high price are other important hurdles behind the low uptake of the higher-valent combination vaccines [ 38 ]. A recent study showed general low awareness of non-NIP vaccines, and awareness of pediatric pentavalent vaccines was lowest [ 39 ]. Based on a study conducted in the well-developed Dongcheng District of Beijing, among 183 parents, only 21.31% (39) had heard of pentavalent vaccine and only 10.93% knew that higher-valent pediatric combination vaccines could substitute for program vaccines [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRC is the second leading cause of cancer deaths in the United States, and more than 34% of CRC patients died in 2023, according to a new report (Siegel et al 2023 ). The new incidence of CRC in China was 12.2% by 2020, and the incidence in urban population was much higher than that in rural areas (Wang et al 2023b ; Zhang et al 2022 ). Currently, it is believed that family heredity, dietary habits, lifestyle and environment may be the predisposing factors of CRC, but the specific etiology has not been clarified (Zhou et al 2022b ).…”
Section: Introductionmentioning
confidence: 99%